Biocatalytic Metal‐Organic Frameworks: Promising Materials for Biosensing. (27th January 2022) - Huang, Wei; Huang, Siming; Chen, Guosheng; Ouyang, Gangfeng
Abstract: The highly efficient and specific catalysis of enzymes allows them to recognize a myriad of substrates, which enables biosensing. However, the fragility of natural enzymes severely restricts their practical applications. Metal‐organic frameworks (MOFs) with porous networks and attractive functions have been intelligently employed as supports to encase enzymes and protect them against harsh environments. More importantly, customizable construction and composition affords the intrinsic enzyme‐like activity of some MOFs (known as nanozymes), which provides an alternative route for the construction of robust enzyme mimics. This review will introduce the concept of these biocatalytic MOFs, with special emphasis on how biocatalytic processes that operate in these materials can reverse the plight of native enzyme‐based biosensing. In addition, the present challenges and future outlooks in this research field are briefly discussed. Abstract : Metal‐organic frameworks (MOFs) with porous networks and attractive functions have been intelligently employed as supports to encase enzymes and protect them against harsh environments. More importantly, customizable construction and composition affords the intrinsic enzyme‐like activity of some MOFs (known as nanozymes), which provides an alternative guideline for constructing robust enzyme mimics. This review will introduce the concept of these biocatalytic MOFs, with special emphasis on how the biocatalytic processes operate in these materials can reverse the plight of native enzyme‐based biosensing.